RANCANG BANGUN GEROBAK SORONG SEMI-OTOMATIS BERPENGGERAK MOTOR DC DENGAN MENGGUNAKAN METODE PULSE WIDTH MODULATION - Yozi Abdullah Haqiqi; I Made Suartika; I Nyoman Setiawan (Jurnal SPEKTRUM, 2022)
The wheelbarrow is a tool for transporting material in mining, plantation, and other areas that is pushed by one person with two rear handles and one wheel in the front. However, its use still requires and relies on a large amount of human power. The workers still have to expend energy to push the wheelbarrow which of course will be very heavy if the load is added in the wheelbarrow. Therefore, it is necessary to add an additional driving force to the wheelbarrow that can help the workers so that they can save their energy and also can make work more efficient. This wheelbarrow will use a DC motor as the driver and use Arduino uno with the PWM method as the control system. In addition, the tool will use a Lithium-ion battery so that it is more durable and can be easily recharged. The battery used has a voltage of 24V and a capacity of 9Ah. This semi-automatic wheelbarrow that uses a dc motor can help work faster up to about 32.5% more efficiently than without using a dc motor. In addition to being more efficient in use, wheelbarrows with dc motors also make it easier for users to use these tools compared to wheelbarrow without dc motors.